Synchronous bidirectional endoscopy for iron deficiency anaemia: is it appropriate for patients under 50?. Issue 1016 (14th April 2010) - Landy, J; Macfarlane, B
Abstract : Background: UK guidelines1 suggest investigation with bidirectional endoscopy (BDE) (upper endoscopy and colonoscopy) in the same sedative episode is a reasonable approach for the investigation of iron deficiency anaemia. There are few data regarding such investigation for iron deficiency anaemia (IDA) in young men. Objective: To assess the use of synchronous BDE for IDA in men and in women <50; and to compare the effectiveness of synchronous BDE in the investigation of iron deficiency anaemia in patients <50 years with those >50 years. Methods: Our endoscopy database was searched for all synchronous bidirectional endoscopies that were undertaken for the indication of iron deficiency anaemia between 2003 and 2009. Age, gender and endoscopic findings were retrieved for each procedure. Significant findings were defined as cancer, grade 3 oesophagitis (Savory Miller classification), oesophageal stricture, Barrett's oesophagus, ulcer, arteriovenous malformation, colitis, and colonic polyps >1 cm. Results: 558 patients underwent synchronous BDE for iron deficiency anaemia between 2003 and 2009. A significant finding in those >50 years was found in 24.6% vs 11.3% of patients <50 years (OR 2.5, 95% CI 1.3 to 5.0). In men under 50 years a significant finding was present in 20.6%. Dual pathology was present in 1.5% of patients over 50 vs 1.3% under 50 years. Conclusions: Our findings suggest that synchronous BDE is an appropriate means of investigation for iron deficiency anaemia in patients >50 and for men <50 years old.